THE CHINESE PRESENCE IN KAZAKHSTAN’S OIL AND GAS INDUSTRY - PARAMONOV, Vladimir; STROKOV, Alexei (CENTRAL ASIA AND THE CAUCASUS, 2015)
China’s presence in Kazakhstan’s oil and gas industry shows that it is primarily interested in developing this country’s hydrocarbon fields. Raising the production volumes of Kazakhstan’s hydrocarbons will make it possible for China to meet its own energy needs. Chinese companies presently control approximately one quarter of the oil produced in Kazakhstan and one fifth of its petroleum product market. They also occupy a relatively strong niche in such an important segment of Kazakhstan’s oil and gas industry as the construction and exploitation of oil and gas pipelines. In the short and medium term, the nature and scope of China’s presence in Kazakhstan’s oil and gas industry is unlikely to significantly change. In the long term, much will depend on whether Chinese companies gain access to “big oil” and, correspondingly, “big gas” after developing offshore deposits, primarily within the framework of the North Caspian project.